GNSS REFLECTOMETRY MEASUREMENT OF SNOW DEPTH AND SOIL MOISTURE IN THE FRENCH ALPS - Boniface, K.; Walpersdorf, A.; Guyomarc'h, G.; Deliot, Y.; Karbou, F.; Vionnet, V.; Nievinski, F. [UNESP]; IEEE (Ieee, 2015)
Over the last ten years Earth observing systems have grown considerably and thus allow the use of Global Navigation Satellite System (GNSS) signals for remote sensing. Several studies in the U.S. have proven the ability of existing GNSS ground networks to measure environmental parameters quantifying essential surface conditions for the understanding of the water cycle. This is possible by taking advantage of reflected signals around geodetic stations. Improved characterization of environmental disturbances in GNSS signals is also essential to increase the accuracy of future GNSS measurement for applications in Earth Sciences. GNSS reflectometry provides these surface parameters at an intermediate scale that can bridge the lack of data between in situ and satellite observations. Here we adapt and develop for the first time the GNSS reflectometry method using the existing sites of the French national GNSS permanent network (RENAG) for snow and soil moisture applications.
Keywords: GNSS; GNSS Remote sensing; Reflectometry; Hydrology